Pengaruh Lingkungan Sosial, Uang Saku, Kontrol Diri Dan Gaya Hidup Terhadap Perilaku Menabung Mahasiswa Universitas Muhammadiyah Sidoarjo - Mochammad Rendy Pamungkas; Sriyono Sriyono; Wisnu Panggah Setiyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Saving is the most appropriate way to face the uncertainties of life's journey. Savings can be considered a savior when the economy is unstable. Good saving behavior is required to have adequate savings. This study aims to determine whether social environment, allowance, self-control, and lifestyle influence the saving behavior of students at Muhammadiyah University of Sidoarjo. This research employs a quantitative method. The population in this study is 11,631 and the sample size is 100 respondents. Random sampling technique is used for sample selection. The data used are primary and secondary data collected through questionnaire distributed via Google Forms. Based on the data analysis results, it is found that the social environment, allowance, self-control, and lifestyle collectively have a positive and significant effect on saving behavior. Social environment positively and significantly affects saving behavior, allowance positively and significantly affects saving behavior, self-control positively and significantly affects saving behavior, and lifestyle positively and significantly affects saving behavior.